Multicentred Systemic Design Pedagogy Through Real-Life Empathy: Integral and Inclusive Practice-Based Education in the Research-by-Design Context - Davidova, Marie (FormAkademisk, 2020)
This article reflects on my integral design studio teaching and inclusiveness in its design processes. This is exemplified in two different systemic design case studies focusing on social and environmental justice via the lens of empathy. The design studio and/or design practice tend to be fused in this article because my design studios have always focused on practice-based, real-life built projects, while my commercial and not-for-profit practices have always implemented design education in real-life built projects through internships and/or other student participation. Therefore, my approach fully follows the pathway of ‘learning by doing’(Dewey, 1997), focusing on systemic feedback looping of integral real-life experience and reflection through research and practice, targeting brighter post-Anthropocene futures.